The Routledge encyclopedia of translation technology - Chan, Sin-Wai (London : Routledge, 2015)
'The Routledge Encyclopedia of Translation Technology provides a state-of-the art survey of the field of computer-assisted translation. It is the first definitive reference to provide a comprehensive overview of the general, regional and topical aspects of this increasingly significant area of study. The Encyclopedia is divided into three parts:Part One presents general issues in translation technology, such as its history and development, translator training and various aspects of machine translation, including a valuable case study of its teaching at a major university; Part Two discusses national and regional developments in translation technology, offering contributions covering the crucial territories of China, Canada, France, Hong Kong, Japan, South Africa, Taiwan, the Netherlands and Belgium, the United Kingdom and the United States Part Three evaluates specific matters in translation technology, with entries focused on subjects such as alignment, bitext, computational lexicography, corpus, editing, online translation, subtitling and technology and translation management systems. The Routledge Encyclopedia of Translation Technology draws on the expertise of over fifty contributors from around the world and an international panel of consultant editors to provide a selection of articles on the most pertinent topics in the discipline. All the articles are self-contained, extensively cross-referenced, and include useful and up-to-date references and information for further reading. It will be an invaluable reference work for anyone with a professional or academic interest in the subject.'--
'Routledge Encyclopedia of Translation Technology is the first definitive reference that provides accurate and useful information on the general, regional, and topical aspects of translation technology in the contemporary world of translation. Leading scholars and specialists in the field from around the world have contributed articles to this encyclopedia. All the articles are self-contained, extensively cross-referenced, and include useful and up-to-date references and information for further reading. With its comprehensive coverage and broad perspectives, Routledge Encyclopedia of Translation Technology is an invaluable reference work for anyone who wants to learn more about the concepts and skills of translation technology for translation practice and academic research'--
Includes bibliographical references and index.
Keywords: Translating and interpreting -- Technological innovations -- Encyclopedias; Translating and interpreting -- Encyclopedias